Colour polymorphism in the terrestrial snail Cepaea nemoralis: from genetics and genomics to spectroscopy and deep learning - Ramos Gonzalez, Daniel (2021)
Colour variation in the animal kingdom has been important in science to determine the principles of biology, especially in genetics and evolution. In the past decades, much effort has been targeted at the evolutionary, ecological and genetic basis of colour variation. Although land snails have been relatively neglected, especially in latter years, a comprehension of genetics and the evolution is important to understand colour variation precisely because snails may be representative of many species. When studying colour polymorphism, one of the remaining challenges is to describe colour. Generally, colour is described manually, relying on the judgment of human perception, classifying them into a discrete types. The main issue, then, is that human perception is subjective and colour is continuous. Fortunately, technology has enabled new techniques to score colour, which may help to investigate colour polymorphism.